MORFOMETRICS OF MALE PASUNDAN CALVES ON DIFFERENT AGES UNDER EXTENSIVE REARING - Kardaya, Dede; Tanjung, Aryo Saputra; Dihansih, Elis (Universitas Djuanda Bogor, 2019)
ABSTRACTThis research on Morphometrics of Male Pasundan on Various Age was carried out in July 2018 in Cibalong District, South Garut Regency, West Java. This study aims to determine the relationship between body size of male calves at various ages and estimation of body weight using body size. The object in this study was 28 male calves at the age of 1-12 months. The results showed a relationship (R2 approaching 1) with the equation of each measurement, namely the Logarithmic regression equation for body lenght and chest deep (96,837ln(x) – 311,88), Polinomial regression equation for body and length body height (-0144x2 + 2,9524x – 48,433), Power regression equation for chest deep and chest girth (0,5317x0,9285), Logarithmic regression equation for body length and chest deep (34,974ln(x) – 110,5), Polynomial regression equation for body height and chest deep (0,004x2 - 0,1438x + 19,89). The result also show that the best model of estimating the body weight of Pasundan cattel is to use the the Polynomial formula with the equation y= 0.218x2 – 2.2536x + 76.074 where x is the size of the calf’s chest girth.Keyword: Extensive, morphometrics, pasundan male calf, weight estimation, polynomial